2022
DOI: 10.3390/life13010074
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Alteration after Neoadjuvant Endocrine Therapy or Chemotherapy in Estrogen Receptor-Positive Breast Cancer

Abstract: In estrogen receptor (ER)-positive breast cancer, changes in biomarker expression after neoadjuvant therapy indicate the therapeutic response and are prognostic. However, there is limited information about the biomarker alteration caused by neoadjuvant endocrine therapy in ER-positive and human epidermal growth factor receptor 2 (HER2)-negative breast cancer. We recruited ER-positive/HER2-negative breast cancer patients who received neoadjuvant chemotherapy (NCT), neoadjuvant endocrine therapy (NET), or sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…AIs therefore had a significant suppressive effect on PR expression. A reduction in PR expression following standard endocrine therapy was previously reported, 8,27 and might imply resistance to endocrine treatment. Ohara et al showed that PR-negative status was independently associated with shorter survival following AIs adjuvant therapy.…”
Section: Discussionmentioning
confidence: 68%
“…AIs therefore had a significant suppressive effect on PR expression. A reduction in PR expression following standard endocrine therapy was previously reported, 8,27 and might imply resistance to endocrine treatment. Ohara et al showed that PR-negative status was independently associated with shorter survival following AIs adjuvant therapy.…”
Section: Discussionmentioning
confidence: 68%
“…Alterations in ER, PR, HER2, Ki67, and p53 have been reported following NAC treatment, with widely varying results from series to series [ 18 , 19 , 21 , 35 , 36 ]. Considering that these biomarkers may change after NAC, we included ER, PR, HER2, Ki67, and p53 both before and after treatment in the pre-NAC and post-NAC multivariate analysis, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to fill this research gap by developing and evaluating novel nomograms for predicting disease-free survival (DFS) based on core needle biopsy and surgical specimens in female BC patients with a non-pCR to NAC. A biopsy at diagnosis and post-NAC residual tumors in patients without a pCR can show discrepancies in receptor status (from negative to positive or vice versa) and changes in biomarker expression [ 18 , 19 ]. Discordances in ER, PR, HER2, Ki67, and p53 can indicate chemosensitivity or chemoresistance as well as have clinical implications for the prognosis and adjuvant therapy [ 18 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Сообщалось, что первичная химиотерапия преимущественно убивает недифференцированные РЭ / РПотрицательные или HER2-положительные [16] опухолевые клетки, таким образом, в значительной степени оставляя РЭ / РП-положительные или HER2-отрицательные опухолевые клетки.…”
Section: Introductionunclassified